Electronic Information Resources: A Case of Designing Virtual Library in Mathematics - Meera, B. M. (Journal of Information and Knowledge, 2002)
The complexities involved due to various formats of Electronic Information Resources are increasing day by day. Information available on Internet is one such evident example posing problems both qualitatively and quantitatively to the user community. Design and development of Virtual Library could be a solution to this problem, which enables customizing.and streamlining the information 'products on the Internet. In this article an attempt has been made to develop Virtual Library in Mathematics, anticipating its utility to the user community.